Construction and Application of Online Learning Resource Incentive Mechanism Driven by Smart Contract - Shukun Liu; Zhimin Liu; Baimu Chen; Xianmin Pan (IEEE Access, 2024)
In the modern era, the significance of incentive mechanisms spans a variety of fields, including the development of smart cities, the dynamics within social information networks, and the realm of online education. This study introduces an innovative incentive strategy, grounded in the use of blockchain contracts, aimed at cultivating reliable interactions among participants while simultaneously bolstering the security and effectiveness of digital learning resources. By capitalizing on the inherently decentralized architecture of blockchain technology, this research unveils a novel approach to digital learning resources, encompassing both the concept and its associated storage framework. Moreover, the study proposes a dynamic optimization model specifically designed for the blockchain of educational resources. This model is crafted to fit seamlessly within the context of real-world educational settings, taking into careful consideration the diverse viewpoints of all stakeholders engaged with particular educational materials. In the realm of practical education, particularly within the domain of computer science, this approach emphasizes the integration of pertinent learning materials into blockchain nodes, thereby addressing key educational content. By implementing a blockchain smart contract, an incentive mechanism is created that rewards both learners and resource contributors, effectively encouraging active participation in resource development and quality improvement. This mechanism effectively tackles challenges in the learning process, such as inaccurate resource access, reduced learning efficiency, and the scarcity of current, high-quality online resources. Experimental findings show that the smart contract-driven online learning resource incentive mechanism significantly improves teaching effectiveness.